Exploring the effects of ageing, cancer, and exercise on skeletal muscle mitochondrial function - Smart, Thomas (2024)
As the worldwide population ages, there becomes a growing prevalence of age associated muscle mass and function, known as sarcopenia. Sarcopenia is well recognised to be associated with poor health outcomes, with reduced life expectancy and worse clinical outcomes well established. The ageing population has also led to an increased prevalence of cancer. Cancer cachexia is the loss of muscle mass and function combined with anorexia caused by malignancy, which is associated with worse clinical outcomes for those undergoing cancer treatment. Given the increasing burden of both sarcopenia and cancer cachexia on worldwide healthcare systems, it is of growing importance to understand the physiology underpinning both conditions. This thesis will explore the role of skeletal muscle mitochondrial oxidative phosphorylation changes in both healthy ageing and in cancer patients.